Retrospective Analysis of Acute Odontogenic Osteomyelitis in Children in the Department of Paediatric Maxillofacial Surgery for the Period 2019-2021 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The problem of odontogenic purulent-inflammatory diseases of the maxillofacial region in children remains urgent due to the large number of patients with this pathology. Despite the improvement of the quality of care, development of new methods of treatment of purulent-inflammatory diseases of the maxillofacial region, the number of patients with this pathology continues to grow in our country.